Optimising assessments of the epidemiological impact in The Netherlands of paediatric immunisation with 13-valent pneumococcal conjugate vaccine using dynamic transmission modelling - De Cao, E; Melegaro, A; Klok, R; Postma, M (Public Library of Science, 2014)
This work is the first attempt to quantify the overall effects of a 13-valent pneumococcal conjugate vaccine (PCV13) vaccination programme in the Dutch population taking into account all the direct and indirect effects of the vaccine on invasive pneumococcal disease. Using available Dutch data, a dynamic transmission model for the spread of pneumococci and potential subsequent invasive pneumococcal disease has been adapted to the Dutch setting. Overall, invasive pneumococcal disease cases in the Netherlands are predicted to decrease from a pre-vaccination level of 2623 cases annually to 2475, 2289, 2185, 2179, and 2178 cases annually 5-, 10-, 20-, 30-, and 40-years, respectively, post-vaccination. Therefore, vaccination with PCV13 in the Netherlands is predicted to lower invasive pneumococcal disease cases per year by up to 445 cases in the medium- to long-term. The results are quite robust for the sensitivity analyses performed on the parameters that regulate herd immunity and competition between vaccine and non-vaccine types.